DEVELOPMENT OF CANVA-BASED INTERACTIVE E-BOOK AND BOOK CREATOR USING THE RADEC LEARNING MODEL TO SUPPORT CREATIVE THINKING SKILLS - Prastyana, Via; Anggoro, Subuh; Prisilawati, Dian Eis; Nazirah, Aliyatun; Cyril, Nelson (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2023)
The involvement of technology in 21st century learning is indispensable at every level of education. Teachers can involve digital learning media to support the process of teaching and learning activities. Digital-based learning media such as interactive e-books can be used as learning media that can be used in 21st century learning. In addition to digital-based learning media, the learning model that can be applied is an innovative learning model. The RADEC learning model is one of the learning models that can be applied in current learning. This study aims to develop an interactive e-book through the RADEC learning model, and determine the feasibility of an interactive e-book through the RADEC learning model. This research is a research and development or Research and Development ADDIE model. This study obtained the feasibility results from the validation of material experts, validation of linguists, and validation of media experts. The results of the validation of material experts, linguists, and media experts get scores in the very valid category for use. The results of student responses regarding product trials get scores in the very interesting category for students to use in the learning process. The results of the group creativity assessment are very interesting and can increase the creativity of students. Based on these results, it can be concluded that interactive e-books through the RADEC learning model are very valid and feasible to be used in learning and can increase students’ creativity.